Complete Remission of Human Parvovirus B19 Associated Symptoms by Loxoprofen in Patients with Atopic Predispositions - Itsuro Kazama; Naoko Sasagawa; Toshiyuki Nakajima (Case Reports in Medicine)
Two cases of women in their thirties with past histories of atopic dermatitis and allergic rhinitis developed a low grade fever, followed by a butterfly-shaped erythema, swelling of their fingers, and polyarthralgia. Despite such symptoms that overlap with those of systemic lupus erythematosus (SLE), the diagnostic criteria for SLE were not fulfilled. Due to positive results for human parvovirus B19 (HPV-B19) IgM antibodies in the serum, diagnoses of HPV-B19 infection were made in both cases. Although acetaminophen failed to improve their deteriorating symptoms, a nonsteroidal anti-inflammatory drug (NSAID), loxoprofen, completely removed the symptoms immediately after the administration. In those cases, since the patients were predisposed to atopic disorders, an increased immunological response based on the lymphocyte hypersensitivity was likely to be involved in the pathogenesis. The immunomodulatory property of NSAID was thought to repress such lymphocyte activity and thus provided a rapid and sustained remission of the disease.